2004
DOI: 10.1136/bjo.2003.029330
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the fixed combination of latanoprost and timolol with the unfixed combination of brimonidine and timolol in patients with elevated intraocular pressure. A six month, evaluator masked, multicentre study in Europe

Abstract: Purpose: To compare the intraocular pressure (IOP) reducing effect and safety of fixed combination (FC) latanoprost/ timolol with unfixed combination (UFC) brimonidine/timolol in patients with increased IOP. Methods: In this 6 month, randomised, evaluator masked, parallel group European study, patients with glaucoma or ocular hypertension and IOP >21 mm Hg on monotherapy or .16 mm Hg on dual therapy received either FC latanoprost/timolol at 8:00AM or UFC brimonidine/timolol at 8:00AM and 8:00PM. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…16 mmHg) on mono-or dual therapy had lower diurnal IOP with FCLT (16.9 mmHg) than concomitant brimonidine and timolol (18.2 mmHg), P , 0.001, at 6 months, 156 also supported by a cross-over study with a 1-month timolol run-in period. 154 Data from 3 Phase III clinical studies 199,200 have shown that the fixed combination of bimatoprost 0.03%/timolol 0.5% (FCBT) ophthalmic solution (Ganfort ® ; Allergan inc., Irvine, CA) was significantly more effective in lowering IOP, with a higher percentage achieving mean reduction in diurnal IOP of .20% or a target pressure of ,18 mmHg, than timolol or bimatoprost monotherapy.…”
Section: Pga/timolol Fixed Combinationsmentioning
confidence: 60%
See 1 more Smart Citation
“…16 mmHg) on mono-or dual therapy had lower diurnal IOP with FCLT (16.9 mmHg) than concomitant brimonidine and timolol (18.2 mmHg), P , 0.001, at 6 months, 156 also supported by a cross-over study with a 1-month timolol run-in period. 154 Data from 3 Phase III clinical studies 199,200 have shown that the fixed combination of bimatoprost 0.03%/timolol 0.5% (FCBT) ophthalmic solution (Ganfort ® ; Allergan inc., Irvine, CA) was significantly more effective in lowering IOP, with a higher percentage achieving mean reduction in diurnal IOP of .20% or a target pressure of ,18 mmHg, than timolol or bimatoprost monotherapy.…”
Section: Pga/timolol Fixed Combinationsmentioning
confidence: 60%
“…Head-to-head trials post-dated the study hence studies comparing the medication in question and timolol 71-73, 81,116,119,147,148 or betaxolol 149 were included. In contrast, head-to-head trials, 43,52,53,59,70,76,77,83,[150][151][152][153][154][155][156][157] only were analyzed for the second meta-analysis. 146 The pooled summary estimate significantly favored latanoprost (weighted mean difference (WMD) = 1.10, 95% CI 0.57 to 1.63) over brimonidine.…”
Section: Vs Brimonidinementioning
confidence: 99%
“…17,28 In the present research, both combination therapies showed a mean IOP-reducing effect from baseline of about 35%. As far as FC latanoprost/timolol is concerned, this level of reduction is toward the high end of the range of decreases found in previous studies 31,[33][34][35][36][37][38][39] with morning dosing and no timolol run-in (range, 31.5-36.0%). With regard to the FC 40 use of systemic b-blockers was not an exclusion criterion in this study if the subject and dosage were stable for 3 months before screening and if the dosage was not expected to change during the study.…”
Section: Fixed-combination Ocular Hypotensives S Miglior Et Almentioning
confidence: 77%
“…A recent 6-month study compared the fixed combination of latanoprost– timolol with concomitant use of brimonidine and timolol in 325 patients. At the 6 month visit, mean IOP was 16.9(standard deviation [SD] 2.8)mm Hg in the fixed combination group and 18.2(SD 3.1) mm Hg in the brimonidine–timolol group (p<0.001) (Garcia-Sanchez et al 2004). …”
Section: Fixed Combinationsmentioning
confidence: 99%